if F(X)=3X-1 AND G(X)=2X^2 +1 WHAT IS F (3)+G(0)?

13 Answers

Relevance
  • raj
    Lv 7
    1 decade ago
    Favorite Answer

    f(3)=3(3)-1=8

    g(0)=2(0)^2+1=1

    so f(3)+g(0)=9

  • Anonymous
    1 decade ago

    F(3)=3(3)-1+G(0)=2(0)^2+1

    9-1+0+1=9

  • Anonymous
    1 decade ago

    F(3) + G(0) = 3*3 - 1 + 2*0*0 + 1 = 9 - 1 + 0 + 1 = 9

  • 1 decade ago

    3(3) - 1 + 2(0^2) + 1 = 9

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 decade ago

    F(3) means x=3 in the F(x) equation so F(3)= 3*3-1.

    G(0) means put x=0 in the G(x) equation so G(0) = 2*0^2 +1.

    add them together and you get 9.

  • Anonymous
    1 decade ago

    9

  • 1 decade ago

    9

  • 1 decade ago

    9

  • 1 decade ago

    *Take each number and replace it with "x" in the equation:

    1. F(3) = 3(3) - 1

    F(3) = 9 - 1

    F(3) = 8

    2. G(0) = 2(0)^2 + 1

    G(0) = 0^2 + 1

    G(0) = 0 + 1

    G(0) = 1

    Second: solve according to order of operations > F(3) + G(0)

    8 + 1 = 9

  • 1 decade ago

    f(3) = 3(3) - 1 = 9 - 1 = 8

    g(0) = 2(0)^2 + 1 = 2(0) + 1 = 0 + 1 = 1

    f(3) + g(0) = 8 + 1 = 9

    f(3) + g(0) = 9

  • 1 decade ago

    f(3)= 3(3)-1

    =9-1

    =8

    g(0)= 2(0)^2+1

    =0+1

    =1

    8+1=9

    9

Still have questions? Get your answers by asking now.